Self-healing materials for potential use in textile and clothing applications - Alena Dannehl; Amelie Buhr; Angela Sanchez Leyton; Lennart Hellweg; Mathias Beer; Lilia (Communications in Development and Assembling of Textile Products)
Self-regenerating, polymer-based textiles emulate living organisms’ ability to heal broken skin and other lesser injuries. To achieve this effect, either intrinsic or extrinsic methods of having polymeric compounds mend these damages can be employed. Depending on the method used, the handling and results of the self-regenerating effect differ. This allows for different areas of application. The focus of this paper is to discuss some of these potential textile applications as well as related research and developments in the area of self-healing materials.